PERANCANGAN SISTEM APLIKASI PEMBELIAN TIKET BIOSKOP PADA CINEMA 21 MELALUI WEBSITE “TIX ID” DAN MENGGUNAKAN SOFTWARE “STAR UML” - Farah Fahrunnisa; Pujo Iswahyudi, Putra Dwi Sunaryanto, Fikri Nurfahrudin, Alif Hidayat (CV. Adiba Aisha Amira, 2024)
The idea to develop this online ticket ordering model emerged from observations and experiences gained in everyday life. For example, from the past until now, audiences who want to buy cinema tickets have to queue at the ticket sales counter to buy cinema tickets. Ironically, this method is relatively ineffective because viewers have to queue in long and long queues to get cinema tickets, but it is not uncommon for before their turn to buy tickets, the tickets they want to buy are sold out without any information regarding the tickets purchased. there still is. Improving service and providing information as a whole, namely by changing the management of providing information regarding tickets that are still available. Initially, customers had to come directly to the cinema, and now the information can be viewed via the web. With this, problem-solving solutions are needed so that the process of watching films in the cinema can be made easier without having to waste excessive time and energy in purchasing tickets. The solution is to order cinema tickets online via the internet.